cognitive references of the directorial imagination and modeling of the theatrical actor performance (Al-Academy, 2017)
This research is determined by the study of the " cognitive references of the directorial imagination and modeling of the theatrical actor performance ." it has described an Iraqi theatrical model, The research began with the great importance of the director's imagination as the basic premise for crystallizing the director's vision according to its cognitive references in creating a solid performance model based on the aesthetic, intellectual and technical bases, It is also contributes to the formation of the theatrical show as a technical framework that presents the show in one unified fabric.The research sought to reach through the problem of research, which is in the question of: What is the modeling of the performance of theatrical representation according to the Cognitive references to the theatrical director, and were they related to the curricula, trends and methods of Scientific or they were Random self-references? For this reason, the research was formulated under the title (cognitive references of the directorial imagination and modeling of the theatrical actor performance).